Predicting Granitic Buried-Hill Reservoirs Using Seismic Reflection data—A Case Study From the Bongor Basin, Southwestern Chad - Wang, Yajie; Xu, Guosheng; Zhou, Wei; Liang, Jiaju; Xu, Fanghao; He, Sai (Frontiers in Earth Science, 2022)
Predicting the distribution of fractured and dissolved reservoirs in granitic buried hills is a prerequisite for finding high-quality hydrocarbon reservoirs and improving the success rate of exploration activities. Granitic buried-hill reservoirs in the Bongor Basin are characterized by strong heterogeneity and poor lateral continuity. Through the analysis of seismic, core, logging and dynamic production data, this study predicts the distribution of fractured reservoirs and fractured-cave reservoirs in the granitic buried hills in the BC Block of the Bongor Basin. In this study, we predict fractured reservoirs using coherence cubes and linearly enhanced attributes and identify fractured-cave reservoirs with single-frequency attribute bodies. Integrated predictions of fractured reservoirs and fractured-cave reservoirs are conducted using attribute fusion techniques. With these methods, good results have been achieved in reservoir prediction in BC buried hills. Furthermore, this study summarizes a set of granitic buried-hill reservoir prediction techniques for densely inverted rift basins in the Central African Rift System.